Implementation of Differentiated Learning to Improve Student Achievement in Indonesian Language Subject for Third Grade at SD Muhammadiyah 3 Pinrang - Suharni Suharni; Nadar Nadar; Saleha Saleha (Edumaspul: Jurnal Pendidikan, 2024)
Differentiated learning constitutes a pedagogical approach that accommodates the diversity of student characteristics, needs, and learning styles to achieve optimal educational objectives. This research aims to analyze the implementation of differentiated learning in enhancing student achievement in Indonesian Language subject for third-grade students at SD Muhammadiyah 3 Pinrang. The methodology employed was classroom action research utilizing Kemmis and McTaggart's spiral design, conducted across two cycles. The research subjects comprised 28 third-grade students at SD Muhammadiyah 3 Pinrang during the 2024/2025 academic year. Data collection techniques encompassed observation, achievement tests, interviews, and documentation. Data analysis was performed descriptively through quantitative and qualitative approaches, comparing pre-test and post-test results across each cycle. Findings demonstrate that differentiated learning implementation significantly enhanced student achievement. During Cycle I, the average student achievement increased from 68.5 to 75.2 with classical completeness reaching 71.4%. In Cycle II, the average achievement improved to 82.3 with classical completeness attaining 89.3%. This enhancement resulted from content, process, and product differentiation aligned with student learning profiles. The research conclusion indicates that differentiated learning effectively improves Indonesian Language achievement among third-grade students by providing meaningful learning experiences tailored to individual student needs.